New Approaches in Social Research. - Grbich, C. (Introducing qualitative methods., 1998)
A practical introduction to the main theories and methods of qualitative research for the health sciences is offered in this book. It covers the full range of conventional and new qualitative methods including ethnography, phenomenology, grounded theory, biography, action research, historical research, discourse analysis and postmodern, poststructuralist and femininst approaches to research. Carol Grbich shows that qualitative methods need to be followed just as rigorously as quantitative methods, providing examples drawn from various health fields. cat copy. A practical introduction to the ma.